2009
DOI: 10.1614/wt-09-036.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Herbicide and Application Timing on Blackberry Control

Abstract: Blackberry is a troublesome species across much of the southeastern United States. Control of blackberry with the pyridine herbicides is often variable among different locations. Experiments were conducted to determine whether application timing, either spring or fall, affected efficacy of the pyridine herbicides triclopyr, fluroxypyr and picloram, and metsulfuron. The pyridine herbicides provided greater control when applied in the fall. At 12 mo after treatment, fluroxypyr plus picloram and fluroxypyr plus t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…McCarty et al (12) reported that applications of triclopyr alone at rates from 0.42 to 1.1 kg/ha provided from 48 to 83% visual control of highbush blackberry ( Rubus argutus Link) 10 to 12 MAT. Ferrell et al (6) also found that triclopyr (1.1 kg/ha), triclopyr + fluroxypyr (0.82 + 0.27 kg/ha), and picloram plus fluroxypyr (0.65 + 0.52 kg/ha) provided approximately 65 to 80% visual control of upright, cane‐type blackberry ( Rubus spp.) while metsulfuron (0.02 kg/ha) provided approximately 90% control of this species 12 MAT.…”
Section: Northern Dewberry Controlmentioning
confidence: 97%
See 3 more Smart Citations
“…McCarty et al (12) reported that applications of triclopyr alone at rates from 0.42 to 1.1 kg/ha provided from 48 to 83% visual control of highbush blackberry ( Rubus argutus Link) 10 to 12 MAT. Ferrell et al (6) also found that triclopyr (1.1 kg/ha), triclopyr + fluroxypyr (0.82 + 0.27 kg/ha), and picloram plus fluroxypyr (0.65 + 0.52 kg/ha) provided approximately 65 to 80% visual control of upright, cane‐type blackberry ( Rubus spp.) while metsulfuron (0.02 kg/ha) provided approximately 90% control of this species 12 MAT.…”
Section: Northern Dewberry Controlmentioning
confidence: 97%
“…Fixed model effects included herbicide treatments, while random effects included environment, replications (nested within environments), and all interactions with environment and replications. Considering environments as random enables inferences about the treatments to be made over a range of environments (2).…”
Section: Evaluating R Flagellaris Control In Tall Fescuementioning
confidence: 99%
See 2 more Smart Citations
“…These include aminocyclopyrachlor, aminopyralid, fluroxypyr, and imazamox. These chemistries have recently been shown to have considerable utility in weedy and invasive plant management (Enloe et al 2008(Enloe et al , 2012Fast et al 2009;Ferrell et al 2009;Minogue et al 2011), and they warrant testing on this woody species. Therefore, our objective was to evaluate the response of Chinese tallowtree to several new herbicides applied via multiple individual plant treatment (IPT) techniques, including cut stump, foliar, and basal bark treatment methods.…”
mentioning
confidence: 99%